2022
DOI: 10.1111/cod.14223
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of Disperse Orange 3 is possible from the textile dye mix present in the Swedish baseline patch test series. A study by the Swedish Contact Dermatitis Research Group

Abstract: Background: The textile dye mix (TDM) 6.6% in petrolatum contains Disperse Blue (DB) 35, Disperse Yellow 3, Disperse Orange (DO) 1 and 3, Disperse Red 1 and 17, and DB 106 and 124. The most frequent allergen in TDM-positive patients is DO 3. Around 85% of para-phenylenediamine (PPD)-allergic dermatitis patients have been positive to DO 3. There has been a discussion to exclude DO 3 from TDM 6.6% because of strong simultaneous reactions to TDM and PPD.Objectives: To study if DO 3 can be excluded from TDM 6.6%.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
(76 reference statements)
2
7
2
Order By: Relevance
“…The role of sex is unclear, with some studies pointing to female sex as an associated factor, 18,19 whereas others point to male sex 11,20 or as in our study, do not find a relation. 7,9,12 Age over 40 or increasing age is linked in various studies, [18][19][20] opposite to our results lacking any association with age. Stingeni et al 11 did not find significant differences concerning atopic dermatitis, aligned with us, but opposite to the studies by Lisi et al 18 and Ryberg et al 19 Along with our research, the vast majority of reported cases are non-occupational.…”
Section: Simultaneous Sensitizationcontrasting
confidence: 99%
See 3 more Smart Citations
“…The role of sex is unclear, with some studies pointing to female sex as an associated factor, 18,19 whereas others point to male sex 11,20 or as in our study, do not find a relation. 7,9,12 Age over 40 or increasing age is linked in various studies, [18][19][20] opposite to our results lacking any association with age. Stingeni et al 11 did not find significant differences concerning atopic dermatitis, aligned with us, but opposite to the studies by Lisi et al 18 and Ryberg et al 19 Along with our research, the vast majority of reported cases are non-occupational.…”
Section: Simultaneous Sensitizationcontrasting
confidence: 99%
“…European studies have evaluated the frequency of allergy to TDM in consecutive patients. Prevalence ranges from 0.4% to 6.9%, with an average of 2%–3%, 2,5–12 which is similar to ours. In a nation‐wide study conducted in Italy from 2018 to 2019, Stingeni et al 11 found a lower prevalence of 1.5%, supporting a decreasing trend of contact sensitization to DDs in Italy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Reactive dyes have been identified by the Ecological and Toxicological Association of Dyes and Organic Pigments Manufacturers (ETAD) as potential respiratory and skin sensitizers and have been shown to cause respiratory difficulties and/or skin sensitization in workers on occupational exposure [8]. These dyes react with body proteins at physiologic pH and temperatures and can act as haptens producing dermal and respiratory sensitization [4 ▪ ,9–10]. Nevertheless, few descriptions of the role of reactive dyes in the development of occupational allergy have been published in recent years.…”
Section: Introductionmentioning
confidence: 99%